A history of the global economy : the inevitable accident - White, Colin (Colin M.); Edward Elgar Publishing (Edward Elgar Pub., Inc., 2018)
Providing an exceptional overview and analysis of the global economy, from the origins of Homo sapiens to the present day, Colin White explores our past to help understand our economic future. He veers away from traditional Eurocentric approaches, providing a truly global scope for readers. A History of the Global Economy takes a holistic, interdisciplinary approach, beyond the narrow application of economic theory, to include the impact of climate change, genetics and culture. The main themes include the creative innovativeness of humans and how this generates economic progression, the common economic pathway trodden by all societies and the complementary relationship between government and the market. The book moves through the four key economic stages of human history - foraging, agriculture, industry and services - to finally examine where the direction of our future may lie. This comprehensive and ambitious book is a must-read for economists, particularly economic historians, as well as anthropology and political history scholars. It not only explores the history and origins of the global economy but also provides a valuable analysis of the current state of economic affairs, making it an ideal book for those wishing to understand more about our ever-evolving global society.
Contents: Preface -- Part I: Introduction -- 1. Finding a common economic pathway -- 2. Transitions and revolutions -- Part II: Beginnings: place and people -- 3. Changing contexts -- 4. The past within us -- 5. The dynamic forager -- Part III: The agricultural phase, from 15000 BC to 1800 AD -- 6. Asking the wrong questions -- 7. The agricultural revolution: 15000BC - 0 -- 8. Innovativeness in agrarian civilisations: 15000BC - 1800AD -- Part IV: Empires and the rise of agrarian civilisations -- 9. The emergence of complex political organisation -- 10. First civilisations 11. The rise of an eastern agrarian civilisation: China -- 12. Imperialism moves westward -- 13. Imperial structures and their finite lifetimes -- 14. A natural experiment - the Americas -- Part V: Commerce as an enabler of modern economic development -- 15. The building of a global world: trade systems before 1500 -- 16. The circle completed: 1500-1800 -- 17. The integration of the global economy: 1700-1900 -- 18. Creative innovativeness in full bloom -- Part VI: The emergence of the modern economy -- 19. The inception of modern economic development -- 20. Stage one - the Industrial revolution in Britain -- 21. More industrial revolutions -- 22. The Asian miracle? -- Part VII: Where are we at? -- 23. Stage two of modern economic development: the service revolution -- 24. Looking backwards in order to peer forwards -- Index.
Includes index.
Description based on print record.
Keywords: Economics -- History; Electronic books